Tensile properties, cell adhesion, and drug release behavior of chitosan-silver-gelatin nanohybrid films and scaffolds - Rana, V. K.; Kushwaha, Omkar S.; Singh, RajPal; Mishra, Satyendra; Ha, Chang-Sik (Macromolecular Research, 2010)
Drug-loaded nanohybrid films and porous scaffolds were prepared using chitosan, Ag nanoparticles and gelatin using a solution casting and freeze-drying method, respectively. Gelatin was used to incorporate the cell onto the surface of the scaffolds and the nanohybrid films. 1-[2-hydroxyethyl]-2-methyl-5-nitroimidazole) (Metronidazole (MTZ) was used as a model drug. The small percentage of Ag nanoparticles in the nanohybrid films and scaffolds produced significantly higher cell proliferation and levels of drug release. The tensile properties showed improvement in strength by Ag nanoparticles reinforcement at the expense of elongation.
Keywords: carcinogenic metronidazole; cell proliferation; chitosan-Ag-gelatin nanohybrids; drug release; nano-hybrids; scaffolds